2022
DOI: 10.1093/jnci/djac190
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk in patients with diverticular disease: A nationwide cohort study

Abstract: BACKGROUND There are little data on diverticular disease and cancer development, other than colorectal cancer. METHODS We conducted a population-based, matched cohort study with linkage of nationwide registers to the ESPRESSO histopathology cohort. We included 75,704 patients with a diagnosis of diverticular disease and colorectal histopathology and 313,480 reference individuals from the general population matched on age, sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…The present MR study found that genetic predisposition to diverticular disease was associated with the increased risks of colorectal cancer and colon cancer in the Finn-Gen population. In line with our findings, a populationbased and matched cohort study which included 389,184 participants found that patients with diverticular disease had an increased risk of colon cancer and the colorectal cancer risk increased mainly in the first year of followup [22]. A systematic review and meta-analysis of observational studies demonstrated the pool prevalence of colorectal cancer was 1.9% in the patients with acute diverticulitis and the risk of colorectal cancer was significantly higher in the patients with complicated diverticulitis [23].…”
Section: Discussionsupporting
confidence: 91%
“…The present MR study found that genetic predisposition to diverticular disease was associated with the increased risks of colorectal cancer and colon cancer in the Finn-Gen population. In line with our findings, a populationbased and matched cohort study which included 389,184 participants found that patients with diverticular disease had an increased risk of colon cancer and the colorectal cancer risk increased mainly in the first year of followup [22]. A systematic review and meta-analysis of observational studies demonstrated the pool prevalence of colorectal cancer was 1.9% in the patients with acute diverticulitis and the risk of colorectal cancer was significantly higher in the patients with complicated diverticulitis [23].…”
Section: Discussionsupporting
confidence: 91%
“…We conclude that ARHGAP15 could be responsible for the association of diverticular disease and cancer that Ma et al reported [1].…”
Section: Discussionsupporting
confidence: 67%
“…Ma et al studied cancer risk in diverticular disease and reported that patients with diverticular disease who have colorectal histopathology, normal or abnormal, have increased risk of overall incident cancer [1]. The cancers included colorectal cancer, lung cancer, pancreatic cancer, and liver cancer.…”
mentioning
confidence: 99%
“…However, Cooper et al reported an association between diverticulosis and increased risk of interval CRC within 6 months after a negative colonoscopy [17]. Ma et al provided the cohort study results with a linkage of diverticular disease with a risk of overall incident CRC [18]. Nakahara et al state that there is no statistical difference in the relationship between colon neoplasms and colonic diverticulosis within the screening program for positive FOBT patients [19].…”
Section: Resultsmentioning
confidence: 99%